BRITAIN’S POLICIES TOWARDS THE EU: INTEGRATION OR FOREIGN POLICY THEORIES? - Van, Chu Thanh (VNU Journal of Foreign Studies; Vol 34 No 5DO - 10.25073/2525-2445/vnufs.4312, 2018)
Together with Brexit has come not only the official spliting of the United Kingdom (UK) from the European Union (EU) but also the question whether scholars and diplomatic officials should approach the relationship between the two partners of the UK and the EU from Integration Theory or Theory of Foreign Policy? This article investigates the effects of both the viewpoints on the practice of certain diplomatic jobs by the UK’s goverments towards the EU from 1972 to 2016 and the research works by scholars in the world on this relationship.